The potential of the amaranth collection maintained at VIR in the context of global plant breeding and utilization trends - D. V. Sokolova; A. E. Solovieva; A. M. Zaretsky; T. V. Shelenga (Вавиловский журнал генетики и селекции)
Amaranth is an ancient crop of the family Amaranthaceae, but it is fairly new to Russia. Its seeds and leaf biomass contain a high-quality gluten-free protein, fatty acids, squalene (a polyunsaturated hydrocarbon), flavonoids, vitamins, and minerals. A comprehensive study of amaranth, enhancement of its breeding, and development of new cultivars will contribute to food quality improvement through the use of plant raw materials enriched for wholesome and highly nutritious components. At present, selection and hybridization still remain the main amaranth breeding techniques. Meanwhile, mutation breeding and polyploidy have been successfully employed to increase its seed yield and protein content. The genes encoding amaranth proteins have been used to produce transgenic plants of potato, bread wheat, and maize. Despite the great potential of amaranth, little research has been dedicated to the study of its genomics, concentrating mainly on the identification of its species diversity. Targets of breeding practice for amaranth include such characteristics as large size and nonshattering of seeds, short stem, earliness, high yield, cold hardiness, synchronized maturation, resistance to pests and diseases, and high nutritional value, including the content and quality of protein, lipids, squalene, and bioactive compounds. A unique collection of amaranth maintained at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) currently incorporates 570 accessions from various countries. For 70 years it has been replenished with local varieties, commercial cultivars, and wild species supplied by collecting missions, research centers, botanical gardens, genebanks, and experimental breeding stations from all over the world. Long-standing studies have resulted in the formation of trait-specific groups of accessions, with high yields of seeds and leaf biomass, earliness, cold hardiness, high protein content in seeds and biomass, short stems, and resistance to seed shattering, earmarked for vegetable or ornamental purposes. The gene pool of amaranth preserved at VIR can provide unlimited opportunities for breeding and meet the needs of the country’s population, enriching the human diet with ingredients produced from such a health-friendly and useful crop.